Effects of Providing Enrichment Cubes to Suckling Pigs in Late Lactation and After Weaning on Post-Weaning Pig Performance - Madie R. Wensley; Mike D. Tokach; Robert D. Goodband; Jordan T. Gebhardt; Jason C. Woodworth; Joel M DeRouchey; Denny McKilligan; Nathan Upah (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 28 litters (241 × 600, DNA) and 356 nursery pigs (241 × 600, DNA; initially 12.5 lb) were used in 28-d trial (4-d pre-weaning and 24-d post-weaning) to determine the effect of providing enrichment cubes (supersized pellets that resemble cattle cubes and range in size from 1.1 to 2.0 in. in length and 0.6 to 0.8 in. in diameter) to suckling pigs in late lactation and after weaning on post-weaning feed intake and growth. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of: 1) pre-weaning treatment (without or with enrichment cubes); 2) post-weaning treatment (with or without enrichment cubes); and 3) body weight category (light or heavy). Overall, providing enrichment cubes to litters pre-weaning did not have a significant effect on piglet weaning weight (P= 0.976) or post-weaning ADG; however, pigs offered enrichment cubes prior to weaning had improved G:F (P= 0.017) in the nursery. Post-weaning cube application had no effect on the growth performance of pigs after weaning. The percentage of pigs that lost weight after weaning was reduced by 11.7 percentage points when pigs were offered enrichment cubes for 3 d post-weaning compared to no cubes (P= 0.002). Conversely, pre-weaning cube application had no effect on the percent of pigs that lost weight after weaning. In summary, providing enrichment cubes to pigs post-weaning appears to encourage activity around the feeder, therefore reducing the percentage of pigs that lost weight after weaning. However, more research is needed to validate these results in a commercial setting and to better understand the effect of reducing the percentage of pigs that lost weight after weaning on morbidity and mortality.
Keywords: performance; pig; sensory attractant; suckling; weaning